Some Properties of the Quotient Singular Value Decomposition (Journal of Computational Mathematics, 2018)
A new derivation is given for the Quotient Singular value Decomposition (QSVD) of matrix pair $(A,B)$ having the same number of columns. Certain properties of the quotient singular values are proved. The relation between the QSVD and the SVD is analyzed in some detail.